2014
DOI: 10.1590/1807-1929/agriambi.v18n12p1235-1240
|View full text |Cite
|
Sign up to set email alerts
|

Doses de fósforo e irrigação na nutrição foliar do cafeeiro

Abstract: O objetivo deste trabalho foi avaliar, em doses crescentes de fósforo, o efeito de lâminas de irrigação no teor foliar de fósforo de cafeeiros em estágio de primeiro ano de produção. O plantio (Topázio MG-1190) foi realizado em janeiro de 2010 e os tratamentos diferenciados a partir de novembro de 2011. Utilizou-se o delineamento experimental em blocos ao acaso com três repetições, com tratamentos dispostos no esquema fatorial 5 x 4 os quais se compunham por cinco lâminas de irrigação correspondentes às fraçõe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Maximum P accumulation (0.015 g hole -1 ) was estimated with the application of a water depth corresponding to 100% ETc, revealing a 87.5% increment compared to the water depth of 40% ETc. Studying the effect of irrigation on P accumulation in coffee, [10] found that 100% ETc replacement led to the highest accumulations of P in the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum P accumulation (0.015 g hole -1 ) was estimated with the application of a water depth corresponding to 100% ETc, revealing a 87.5% increment compared to the water depth of 40% ETc. Studying the effect of irrigation on P accumulation in coffee, [10] found that 100% ETc replacement led to the highest accumulations of P in the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…The highest phosphorus (P) concentration occurred in the leaves (0.63 g kg -1 ) at 145 DAT, stems (0.47 g kg -1 ) at 180 DAT, and roots (0.57 g kg -1 ) at 159 DAT ( Fig 5). The higher accumulation of P in leaves was likely because of the high P mobility within the plant (Dominghetti et al, 2014), with P transported from older to younger tissues during P deficiency. A higher P concentration in leaves (2.63 g kg -1 ) was also found in 10-week-old Pilea sinofasciata plants grown in non-mineral soils (Zheng et al, 2014).…”
Section: Macronutrient Concentrations In Plant Tissuesmentioning
confidence: 99%
“…When considering quantity and quality of the produced coffee, several factors can influence its production, among them, the nutritional status of the plant is of utmost importance for management strategies definition (Silva et al, 2010). Conventionally, large amounts of nutrients are required by this crop, whose demand is mainly represented by nitrogen (N), potassium (K), and phosphorus (P), which if properly managed can provide well developed and vigorous plants (Silva et al, 2010;Dominghetti et al, 2014;Pérez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%